The Kuda Kepang Turonggo Budoyo Dance in Dharmasraya as a Space for Social Interaction - Pipit Supriyani; Budi Setiyono (Universitas Negeri Medan, 2026)
Dharmasraya Regency became one of Indonesia's major transmigration destinations during the New Order period, resulting in a multicultural society composed of Javanese, Minangkabau, Batak, Sundanese, and other ethnic communities. Within this diverse social setting, cultural practices have become important media for fostering interaction and social cohesion. One of these cultural practices is the Kuda Kepang Turonggo Budoyo (PDC) performance, which has developed in Nagari Kurnia Koto Salak, Sungai Rumbai District. This study examines how the Kuda Kepang Turonggo Budoyo (PDC) performance functions as a space for social interaction among the multi-ethnic community of Dharmasraya. The research employs Herbert Blumer's theory of symbolic interaction and adopts a qualitative approach through field observations, in-depth interviews, documentation, and literature review. Data were analyzed descriptively by interpreting the relationships between the performance structure and the social interactions surrounding it. The findings reveal that although the performance preserves the essential characteristics of the Javanese Kuda Kepang tradition, it has undergone adaptation within the multicultural context of Dharmasraya. The performance incorporates distinctive choreographic movements, musical accompaniment, costumes, and performance properties while simultaneously accommodating the participation of individuals from different ethnic backgrounds. More importantly, the performance serves not merely as an artistic expression but as a social arena where members of diverse ethnic communities interact, collaborate, negotiate cultural meanings, and strengthen social relationships. Therefore, Kuda Kepang Turonggo Budoyo (PDC) functions as both a cultural performance and an inclusive medium that promotes social integration and reinforces community cohesion within Dharmasraya's multicultural society.